Studi Deskriptif Kuantitatif Prokrastinasi Belajar pada Pelaku Adiksi Internet - Annisa Rahmi; Kharisma Safitri; Reza Anugrah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Study procrastination is the deliberate postponement of tasks to the point of subjective discomfort. This study aims to provide useful insights for educators, counselors, and practitioners in designing effective interventions to help individuals overcome study procrastination associated with internet addiction, thereby improving their academic performance and psychological well-being. The hypothesis of this study is to see whether most internet addicts have a high level of study procrastination or not. The research population is 2021 psychology students, Campus V UNP Bukittinggi. The research sample amounted to 11 students. The sampling technique used was purposive sampling. The data collection tool used is the Procrastination Assessment Scale-Students scale (16 valid items). Data analysis using descriptive statistics. The results of data analysis show that there is a significant relationship between internet addiction and study procrastination in students at a high level of study procrastination (63,6%)